2007
DOI: 10.1111/j.1745-7270.2007.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia-mediated DNA Hypomethylation and its Potential Epigenetic Role in Rats

Abstract: Hyperhomocysteinemia (HHcy), which is an independent risk factor for atherosclerosis, might cause dysregulation of gene expression, but the characteristics and key links involved in its pathogenic mechanisms are still poorly understood. The objective of the present study was to investigate the effect of HHcy on DNA methylation and the underlying mechanism of homocysteine (Hcy)-induced DNA methylation. HHcy was induced in Sprague-Dawley rats after 4 weeks of a low, medium or high methionine diet. The levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 43 publications
0
40
0
2
Order By: Relevance
“…However, the exact molecular mechanisms remain to be elucidated. In our previous study, Hcy was found to be involved in the disturbance of the expression of the LDL-receptor promoter region and global genome DNA hypomethylation through the interference of DNA methylation (25)(26)(27). Increasing evidence also suggests that aberrant DNA methylation around promoter regions can lead to the development of AS (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact molecular mechanisms remain to be elucidated. In our previous study, Hcy was found to be involved in the disturbance of the expression of the LDL-receptor promoter region and global genome DNA hypomethylation through the interference of DNA methylation (25)(26)(27). Increasing evidence also suggests that aberrant DNA methylation around promoter regions can lead to the development of AS (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, deprived intake of essential nutrition, which supply the methyl groups from methyl folate or vitamin B12 and cause hyperhomocysteinemia or high level of tHcy.HHcy in depression indicates a breakdown in the methylation of homocysteine to methionine or cysteine, taurine, and glutathione -a B6 -dependent process and causes oxidative stress resulting in neurological and vascular damage and lead to disturbance in the optimal biosynthesis of neurotransmitters and cell signalling or cell repair and also disturbed the level of MAO in brain, its higher concentration as neurotoxic [24]. It is associated with various cardiovascular and other neurologicaldisorders, including cognitive impairment and dementia conversely, accumulation of tHcy involved in the path physiology of depression and reduces the level of neurotransmitters such as serotonin, dopamine, noradrenalin, and γ aminobutyric acid (GABA) are often associated with depression [10,[12][13][14]25,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies has shown that elevation of plasma Hcy correlates with increased AdoHcy levels and with a decreased MP [16]. The low MP is associated with a decreased global DNA methylation [17,18] and these epigenetic changes can lead to inappropriate gene expression and promotion of disease [19,20]. However, a case of AdoHcy-hydrolase deficiency was reported in which the patient's leukocyte DNA was hypermethylated relative to controls despite extremely high levels of plasma AdoHcy [21].…”
Section: Introductionmentioning
confidence: 99%